Legality's borders an essay in general jurisprudence - Culver, Keith Charles, 1969-; Giudice, Michael (New York ; Oxford : Oxford University Press, 2010)
This text explains the rudiments of an inter-institutional theory of law, a theory which finds legality in the interaction between legal institutions, whose legality we characterize in terms of the kinds of norms they use rather than their content or system-membership.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Jurisprudence; Law -- Philosophy